Intramural Ganglion Structures in Esophageal Atresia: A Morphologic and Immunohistochemical Study - Biagio Zuccarello; Antonella Spada; Nunzio Turiaco; Daniela Villari; Saveria Parisi; Isabella Francica; Carmine Fazzari; Federica Pederiva; Juan A. Tovar (International Journal of Pediatrics)
Introduction and Aim. Disorders of esophageal motility causing dysphagia and gastroesophageal reflux are frequent in survivors to esophageal atresia (EA) and distal tracheoesophageal fistula (TEF). The aim of the present study was to investigate the histologic and immunohistochemical features in both esophageal atretic segments to further understand the nature of the motor disorders observed in these patients. Material and Methods. Esophageal specimens from 12 newborns with EA/TEF and 5 newborns dead of unrelated causes were examined. The specimens were fixed in 5% buffered formalin, included in paraffin and cut in 5 micron sections that were stained with hematoxilin and eosin (H and E), and immunohistochemical stainings for Actin, S-100 protein, Neurofilament, Neuron-Specific-Enolase, Chromogranin A and Peripherin were evaluated under the microscope. Results. In controls, the distribution of the neural elements was rather homogenous at both levels of the esophagus. In contrast, the atretic segments showed quantitative and qualitative differences between them with sparser nervous tissue in the distal one in comparison with the proximal one and with controls. Conclusions. These results further support the assumption that histomorphological alterations of the muscular and nervous elements within the esophageal wall might contribute to esophageal dysmotility in patients surviving neonatal operations for EA/TEF.